The Role of Convenience and Usability in the Adoption of Electronic Management Systems: A Theoretical and Empirical Review - Budiyanto, Wasis; Rahayu, Meika Kurnia Puji; Widowati, Retno (Asian Journal of Applied Business and Management, 2024)
This study aims to analyze the role of convenience and usability in the adoption of electronic management systems (EMS) through a scientometric approach. Using a bibliometric analysis of 1,112 articles published in the Scopus database between 2014 and 2024, this study maps the thematic evolution, trends, and main clusters in the related literature. Topic network visualization techniques using VOSviewer and RStudio were used to identify dominant themes and reveal relationships between topics, such as technology acceptance model (TAM), artificial intelligence (AI), blockchain, and other emerging technologies. The results show that convenience and ease of use continue to be key factors in EMS adoption, especially in sectors such as e-commerce, education, and healthcare. The emergence of new issues such as trust, risk, and privacy signals a shift in the focus of recent research, reflecting the need to consider psychological and social factors in modern technology. The theoretical implications suggest that while traditional models such as TAM are still relevant, the integration of new factors such as user satisfaction and privacy is becoming increasingly important.